The role of female Islamic preachers in shaping the character of muslim mothers - Sembiring, Masdalifah; Gandhi, Al Mutia (Jurnal Anifa: Studi Gender dan Anak, 2025)
This study examines the role of female Islamic preachers in shaping the personality of Muslim mothers within the family context. Employing a qualitative approach, the research involved in-depth interviews with three prominent female preachers in Langsa. The findings reveal that female preachers significantly contribute to enhancing mothers’ understanding of religious values, which in turn fosters the development of positive character traits such as patience and compassion. These preachers utilize interactive sermon methods that enable mothers to better comprehend and apply Islamic teachings in their daily lives. The study aims to provide deeper insights into the ways female Islamic preachers support the personal and spiritual growth of mothers within the household sphere.